Botswana Social Accounting Matrix (SAM), 2007 - International Food Policy Research Institute (International Food Policy Research Institute, 2014)
The Botswana Social Accounting Matrix (SAM), 2007 is an update of the official 1996/97 and 2002/03 SAM. It separates 32 activities and 32 commodities; labor is disaggregated by 5 occupation groups; and household into 6 groups based on the rural/urban and income status of the household head. This SAM is a useful database for conducting economywide impact assessments, including SAM-based multiplier analysis and computable general equilibrium (CGE) modeling.